RAP enquanto performance: Um evento de comunicação e expressão musical - Andréa Cristina Cirino (Universidade Estadual de Campinas, 2012)
The text aims to show the rap as a performance that transmits the discourse of a periphery that claims by freedom and social justice through artistic language. Expressive elements are observed in three examples that are part of national rap, influenced by hip hop culture. Based on the theoretical assumptions of Dayrell; Schechner; Zumthor; Carlson; the literature reviewed comes to meet of reflections that indicate the importance of this musical style that implies practices and representations in the historical-cultural context. Under the perspective of music making, we can check the relation ship between language, gestures and art. It is concluded that the rap is no longer a local reality, conquering its space world wide